Analysis and Critical Evaluation of The Strategic Commodity Dossier (SCD) at Jaguar Land Rover - Yeggina, Jayadeva Ashok Kumar (2011)
Organizations across the globe are looking at strategic sourcing as the medium through which they can achieve significant cost savings. This coupled with negotiation tactics helps organizations to achieve better results. Jaguar Land Rover uses a document called SCD in order to derive sutiable sourcing and negotiation strategies. The report analyses and critically evaluates the structure of the SCD for different commodities used in JLR.